Model Kolaborasi Pemerintah dan Komunitas dalam Rehabilitasi Pasca Kebakaran Hutan di Gunung Tampomas - Algie Rahmawan Hidayat; Dewi Noor Azijah; Lolita Deby Mahendra Putri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the government’s role in post-disaster mitigation of forest fires on Mount Tampomas, Sumedang. Frequent forest fires reveal suboptimal post-disaster mitigation efforts despite the regulatory role of the Regional Disaster Management Agency (BPBD). A qualitative intrinsic case study method was employed to analyze this phenomenon using primary and secondary data, interviews, field observations, and documentation. Findings show that BPBD’s involvement was limited to emergency response, while rehabilitation and reconstruction efforts were largely carried out voluntarily by community groups, NGOs, and nature enthusiasts. Key challenges include limited resources, lack of technical knowledge, and insufficient formal training on post-disaster mitigation. Funding for mitigation mainly comes from non-governmental initiatives that play a crucial role in environmental recovery. The study recommends improved coordination among stakeholders, enhanced capacity building and training on post-disaster rehabilitation, and dedicated regulations and funding allocations to support community-based mitigation efforts as part of a sustainable disaster management strategy.